2017
DOI: 10.1097/ico.0000000000001297
|View full text |Cite
|
Sign up to set email alerts
|

Use of Topical Insulin to Treat Refractory Neurotrophic Corneal Ulcers

Abstract: Purpose To report the clinical course of 6 patients with refractory neurotrophic corneal ulcers that were treated with topical insulin drops. Methods Retrospective chart review of patients who had neurotrophic corneal ulcers or epithelial defects refractory to standard medical and surgical treatment. Insulin drops, prepared by mixing regular insulin in artificial tears with a polyethylene glycol and propylene glycol base at a concentration of 1 unit per mL, were prescribed 2–3 times daily. Results Six pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 9 publications
1
61
0
2
Order By: Relevance
“…More recently, Wang and colleagues reported on a small case series of six human subjects with refractory corneal ulcers (59). Patients ranged in age from 2 to 73 years and all presented to clinic with non-healing neurotrophic corneal ulcers.…”
Section: Insulin and The Diabetic Corneamentioning
confidence: 99%
“…More recently, Wang and colleagues reported on a small case series of six human subjects with refractory corneal ulcers (59). Patients ranged in age from 2 to 73 years and all presented to clinic with non-healing neurotrophic corneal ulcers.…”
Section: Insulin and The Diabetic Corneamentioning
confidence: 99%
“…1 Corneal adverse effects occur far less frequently, with only rare reports of brimonidine-related peripheral corneal neovascularization and deep stromal opacification. 2,3 To the best of our knowledge, we describe the first reported case of a brimonidine user developing multifocal corneal subepithelial infiltrates.…”
Section: Footnotes and Disclosurementioning
confidence: 93%
“…Bastion and Ling 5 suggested that 50 IU/mL topical insulin might improve the rate of epithelial wound healing, whereas Fai et al 6 found that dilutions of 25 IU/mL was associated with better healing. As discussed by Wang et al, 3 it is likely that insulin drops may benefit patients with NK of heterogeneous etiologies, other than diabetic neuropathy.…”
Section: Topical Insulin For Neurotrophic Corneal Ulcersmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be used on its own or in a combined solution with umbilical cord blood and has been shown to successfully accelerate corneal epithelial healing in animal and human corneas [74,[76][77][78][79]. Isolated cases of successful resolution of epithelial defects with topical insulin and topical coenzyme Q10 in refractory cases of NK have been reported [80,81]. The underlying mechanism remains unknown; however, topical insulin decreased the rate of sub-basal corneal plexus loss in diabetic mice and promoted epithelial cell migration in in vitro models [82,83].…”
Section: Additional Medical Therapiesmentioning
confidence: 99%